2017
DOI: 10.31234/osf.io/3c2af
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partition dependence in consumer choice: Perceptual groupings do not reliably shape decisions

Abstract: The partitioning of options into arbitrary categories has been shown to influence decisions about allocating choices or resources among those options; this phenomenon is called “partition dependence.” While we do not call into question the validity of the partition dependence phenomenon in the present work, we do examine the robustness of one of the experimental paradigms reported by Fox, Ratner, and Lieb (2005, Study 4). In three experiments (N = 300) conducted here, participants chose from a menu of perceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
5
1
Order By: Relevance
“…Previous work in our lab used the candy choice paradigm to test for partition dependence in children's choices. However, not only did we fail to find evidence of partition dependent choice in children, but in three experiments we did not replicate the previously reported findings of adult partition dependence in this task (Reichelson, Zax, Bass, Patalano, & Barth, 2017). This work shows that the candy choice task itself does not reliably elicit partition dependence, even in adults-leaving open the question of whether partition dependence in decision making occurs in children.…”
contrasting
confidence: 94%
See 2 more Smart Citations
“…Previous work in our lab used the candy choice paradigm to test for partition dependence in children's choices. However, not only did we fail to find evidence of partition dependent choice in children, but in three experiments we did not replicate the previously reported findings of adult partition dependence in this task (Reichelson, Zax, Bass, Patalano, & Barth, 2017). This work shows that the candy choice task itself does not reliably elicit partition dependence, even in adults-leaving open the question of whether partition dependence in decision making occurs in children.…”
contrasting
confidence: 94%
“…Most findings of partition dependence concern complex, formal decision situations. Perhaps partition dependence is less likely in the decision situations available to children (an idea that finds some support in the repeated lack of partition dependence in both children's and adults' choices in candy choice tasks; Reichelson et al, 2017). It is also possible that attention to higher order partitions (vs. individual choice options) does not occur early in life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Simple choices of candies from an arrangement of bowls were reported to exhibit partition dependence in one study [1], but no such effect was found in three recent replication attempts, including one with very closely matched methods [11]. None of the established factors known to reduce partition dependence appeared to play a role in this study (e.g., expertise or greater intrinsic preferences; [1,12]), showing that physical partitions like those utilized in the candy bowl study did not reliably influence consumer choice [11]. Simple selections for consumption from menus of physically partitioned options, therefore, do not necessarily produce partition dependent behavior as had previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One goal of the present work, therefore, is to replicate the findings of a previous study that reported partition dependent behavior. The consumer choice studies in which partition dependence findings were not replicated [11] made use of a relatively simple, straightforward selection task. For the present work, we aimed to move from consumer choice to an allocation task, while continuing to use a relatively simple, straightforward paradigm to attempt to replicate findings of partition dependence in adults' decisions.…”
Section: Introductionmentioning
confidence: 99%